A Comprehensive Study for the Laser Cleaning of Corrosion Layers due to Environmental Pollution for Metal Objects of Cultural Value: Preliminary Studies on Artificially Corroded Coupons. (30th January 2007) - Siatou, A.; Charalambous, D.; Argyropoulos, V.; Pouli, P.
Abstract : This paper is focused on the systematic investigation of the layer-by-layer removal of corrosion products on artificially corroded metal coupons aiming to introduce a methodology for the optimum laser cleaning approach of historical metal objects. Thus, it is very important to determine the chemical composition of the studied surfaces before and after irradiation. A series of laser cleaning studies has been performed on test coupons (reference and artificially corroded). Wavelength and pulse duration effects are investigated. Initial studies were focused on the use of infrared (1064 nm) and ultraviolet (355 nm and 248 nm) radiations of nanosecond ( ns ) pulse duration. Damage and removal threshold values were determined for the substrates and the corrosion layers, respectively. The irradiated surfaces are evaluated microscopically under the optical and the scanning electron microscope, while the mineralogical and chemical composition of the various layers is determined with X-ray diffraction and SEM-EDAX analyses, respectively. The results obtained are providing a comprehensive approach for understanding the main mechanisms that are significant in the different laser cleaning regimes, while the optimum cleaning methodologies for the studied materials are being established.